Design and construction of a 500 W wind turbine with permanent magnets for small electrical demands in rural areas - González Chávez, Salomé (2006)
The present work deals with the design, construction and characterization of a 500 W wind turbine prototype, using national technology. It includes the design and manufacture of each of the components of the wind turbine system - permanent magnet generator, wind rotor and steering elements; as well as the field evaluation to determine its performance. Its application is presented as an energy and socioeconomic solution for rural areas that have wind resources, thus contributing to the improvement of living conditions under the principle of taking advantage of local resources and preserving the environment. As results of the field tests we have the verification of the design conditions as well as its operation according to the wind resource. Although the system was dimensioned to reach a nominal power of 500 W at a wind speed of 8 m/s, in the field this power has been obtained at a wind speed of 8.3 m/s, and a stable behavior in the other conditions.